The Development of Teachers in Learning Through Professional Learning Community Process According to the Kalyanamit 7 Principle of Private Schools Under the Officeof Education, Region 12 - Arthanying, Nittaya; Vadasuddo, PhraHonda; Visitthapanyo, PhramahaPhisit (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to: 1) study the current and desired conditions, as well as the needs for teacher development in instructional management through the Professional Learning Community (PLC) process in private schools within the Inspectorate 12 area, 2) develop a teacher development model for instructional management through the PLC process based on the seven principles of Kalyanamitta Dhamma in private schools within the Inspectorate 12 area, and 3) evaluate the teacher development model for instructional management through the PLC process based on the seven principles of Kalyanamitta Dhamma in private schools within the Inspectorate 12 area. The research employed a mixed-methods approach, incorporating both quantitative and qualitative methods. The sample group consisted of 539 administrators and teachers. The data collection tools included questionnaires, semi-structured interviews, and evaluation forms. Data analysis was conducted using statistical methods to determine the mean, standard deviation, need index, and content analysis. The research results revealed the following: 1) The most pressing need for teacher development in instructional management through the PLC process in private schools within Inspectorate 12 was teamwork, followed by support, shared leadership, and peer collaboration. 2) The developed teacher development model for instructional management through the PLC process based on the seven principles of Kalyanamitta Dhamma included components such as the model's name, objectives, principles, content, and expected outcomes. Key elements of the model were shared values and vision, peer collaboration, support and shared leadership, and teamwork. 3) The evaluation of the teacher development model based on the seven principles of Kalyanamitta Dhamma indicated that the model was accurate, feasible, and highly beneficial.